Outcomes After Extracorporeal Cardiopulmonary Resuscitation of Pediatric In-Hospital Cardiac Arrest: A Report From the Get With the Guidelines-Resuscitation and the Extracorporeal Life Support Organization Registries. Issue 4 (April 2019) - Bembea, Melania M.; Ng, Derek K.; Rizkalla, Nicole; Rycus, Peter; Lasa, Javier J.; Dalton, Heidi; Topjian, Alexis A.; Thiagarajan, Ravi R.; Nadkarni, Vinay M.; Hunt, Elizabeth A.
Abstract : Objectives: The aim of this study was to determine cardiac arrest– and extracorporeal membrane oxygenation–related risk factors associated with unfavorable outcomes after extracorporeal cardiopulmonary resuscitation. Design: We performed an analysis of merged data from the Extracorporeal Life Support Organization and the American Heart Association Get With the Guidelines—Resuscitation registries. Setting: A total of 32 hospitals reporting to both registries between 2000 and 2014. Patients: Children younger than 18 years old who suffered in-hospital cardiac arrest and underwent extracorporeal cardiopulmonary resuscitation. Interventions: None. Measurements and Main Results: Of the 593 children included in the final cohort, 240 (40.5%) died prior to decannulation from extracorporeal membrane oxygenation and 352 (59.4%) died prior to hospital discharge. A noncardiac diagnosis and preexisting renal insufficiency were associated with increased odds of death (adjusted odds ratio, 1.85 [95% CI, 1.19–2.89] and 4.74 [95% CI, 2.06–10.9], respectively). The median time from onset of the cardiopulmonary resuscitation event to extracorporeal membrane oxygenation initiation was 48 minutes (interquartile range, 28–70 min). Longer time from onset of the cardiopulmonary resuscitation event to extracorporeal membrane oxygenation initiation was associated with higher odds of death prior to hospital discharge (adjusted odds ratio for each 5 additional minutes of cardiopulmonary resuscitation prior to extracorporeal membrane oxygenation initiation, 1.04 [95% CI, 1.01–1.07]). Each individual adverse event documented during the extracorporeal membrane oxygenation course, including neurologic, pulmonary, renal, metabolic, cardiovascular and hemorrhagic, was associated with higher odds of death, with higher odds as the cumulative number of documented adverse events during the extracorporeal membrane oxygenation course increased. Conclusions: Outcomes after extracorporeal cardiopulmonary resuscitation reported by linking two national registries are encouraging. Noncardiac diagnoses, preexisting renal insufficiency, longer time from onset of the cardiopulmonary resuscitation event to extracorporeal membrane oxygenation initiation, and adverse events during the extracorporeal membrane oxygenation course are associated with worse outcomes. Abstract : Supplemental Digital Content is available in the text.